Analisis Statistik Untuk Mendapatkan Waktu Losstime Optimal Peralatan Tambang Untuk Memenuhi Target Produksi Pengupasan Overburden di Pit 3 Timur Satuan Kerja Penambangan Elektrifikasi Shovel and Truck PT. Bukit Asam Tbk - Rahmad Fajri; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Based on the overburden stripping production data at Pit 3 East, Electrification Mining Work Unit Shovel and Truck of PT. Bukit Asam Tbk. June 2019 for 4 mining fleet, are around 994.792,50 Bcm. From the actual production above, it is known that the overburden stripping production target for 4 mining fleet is 1.300.000 Bcm, so it can be concluded that the overburden stripping production target in June 2019 is not reached. Based on the data from mining equipment working hours, a percentage of consecutive utilization of available working time of the EU (Effective Utilization) for 4 mining fleet is 26.28%; 58.03%; 57.21% and 60.38%. From these problems, the percentage of utilization of available working time EU (Effective Utilization) cannot be utilized optimally. From the problems above, it is necessary to analyze the optimal losstime to fulfill the overburden stripping production target. As for, the analysis that will be used in this study is multiple linear regression analysis which is using the least squared method in estimating the coefficient of multiple linear regression. The purpose of the analysis is to obtain an optimal losstime mathematical model in fulfilling the overburden stripping production target in June 2019.Keywords: Produksi, Losstime, Waktu Optimal, Analisis Regresi Linear Berganda, Least Squared